High-thermal-conductivity gel containing modified filler and preparation method of high-thermal-conductivity gel

By using modified fillers and composite nanosheets in thermal conductivity gels, the thermal network structure and mechanical properties are enhanced, and the problem of insufficient thermal conductivity coefficient of existing thermal conductivity is solved, and the improvement of high thermal conductivity and mechanical strength is achieved. Develop application requirements in high temperature environments.

CN119220220AInactive Publication Date: 2024-12-31BOSEN NEW MATERIALS (YANTAI) CO LTD

Patent Information

Application Number
CN202411779093.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing thermal conductivity coefficient of the thermal conductivity gel is small and cannot meet the high requirements for heat dissipation performance of high voltage electrical appliances and high-power motors.

Method used

Using a high thermal conductivity gel containing modified fillers, the modified large-particle spherical alumina powder, modified small-particle spherical alumina powder, modified angular alumina powder and graphene oxide/boron nitride composite nanosheets are combined. The filler enhances the thermal network structure and mechanical properties of the gel, and combines with platinum catalyst to accelerate the cross-linking reaction to form a highly thermally conductive gel.

Benefits of technology

It significantly improves the thermal conductivity and mechanical properties of the gel, enhances the thermal conductivity and toughness of the material, and meets the long-term working needs in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, in particular to high-thermal-conductivity gel containing modified filler and a preparation method of the high-thermal-conductivity gel. Organic silica gel is taken as a main body, the curing rate is moderate, no selectivity is caused to a base material, a silane coupling agent is introduced to modify thermal-conductivity filler powder, the compatibility of particles and a silica gel matrix is enhanced, and the thermal conductivity of the high-thermal-conductivity gel is improved; the heat conductivity of the sample is further improved, and the reasonable filler grading is beneficial to the filler to form more heat-conducting passages or heat-conducting networks in a polymer matrix, so that the transmission rate of phonons in the material is enhanced, and the heat conductivity of the composite material is enhanced; through combination of the modified large-particle-size spherical alumina powder, the modified small-particle-size spherical alumina powder and the modified angular alumina powder, a heat-conducting network structure in the gel can be improved, and the filler is modified through the modifier, so that the interface bonding force between the filler and a silicone oil matrix can be enhanced; and the heat conduction efficiency is improved on the basis of reducing the thermal resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to a high thermal conductivity gel containing modified fillers and a preparation method thereof. Background Art

[0002] With the advancement of science and technology, high-voltage electrical appliances and high-power motors are developing in the direction of large capacity, miniaturization, high-power integration, etc., which puts forward higher requirements on the heat dissipation performance of the equipment; during the operation of motors and electrical appliances, high temperature will reduce the electrical properties, mechanical properties and service life of insulating materials. Silicone thermal conductive gel is a kind of siloxane composition with bonding and sealing properties. It is generally cured by adding different silicone matrices, additives and fillers under heating, room temperature or radiation conditions. Thermal conductive gel is a kind of adhesive. Thermal conductive gel inherits the advantages of silicone material such as good affinity, weather resistance, high and low temperature resistance and good insulation. At the same time, it has strong plasticity and can meet the filling of uneven interfaces. It can meet the heat transfer requirements of various applications. The product has low stress and high compression modulus when in use, and can realize automated production; it has good contact with electronic products when assembled, showing low contact thermal resistance and good electrical insulation properties. The cured thermal conductive adhesive is equivalent to a thermal conductive gasket, which has good high temperature resistance and aging resistance. It can work for a long time at temperatures between -40 and 200°C. Therefore, it is widely used in consumer electronics, communication networks, power supplies, automotive electronics, medical, transportation, aerospace and other industries.

[0003] At present, there are many types of thermal conductive gel products on the domestic market. With the development of the electronic technology industry, the demand for thermal conductive gel continues to increase, and the development prospects are very broad. However, the thermal conductivity of similar products on the market is relatively small, so it is necessary to develop a gel with high thermal conductivity to meet market demand. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a high thermal conductivity gel containing modified fillers and a preparation method thereof, which can effectively solve the problem of low thermal conductivity of the thermal conductive gel in the prior art.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A high thermal conductivity gel containing a modified filler, wherein the high thermal conductivity gel containing a modified filler is composed of a main agent system and a curing agent system; The main agent system is composed of the following components: 7-8 parts by weight of low-viscosity vinyl silicone oil, 2-3 parts by weight of high-viscosity vinyl silicone oil, 4-5 parts by weight of terminal hydrogen silicone oil, 0.1-0.3 parts by weight of cross-linked hydrogen silicone oil, 47-49 parts by weight of modified large-particle spherical alumina powder, 23-25 ​​parts by weight of modified small-particle spherical alumina powder, 7-9 parts by weight of modified angular alumina powder, 3-5 parts by weight of graphene oxide / boron nitride composite nanosheets, and 0.02-0.04 parts by weight of inhibitor; The curing agent system is composed of the following components: 12-13 parts by weight of low-viscosity vinyl silicone oil, 47-49 parts by weight of modified large-particle spherical alumina powder, 23-25 ​​parts by weight of modified small-particle spherical alumina powder, 7-9 parts by weight of modified angular alumina powder, 0.1-0.2 parts by weight of platinum catalyst and 1-2 parts by weight of blue slurry.

[0006] Furthermore, the viscosity of the low-viscosity vinyl silicone oil is 500 cps, and the vinyl content is 0.43%. The viscosity of the high-viscosity vinyl silicone oil is 5125 cps, and the vinyl content is 0.17%. The hydrogen content of the hydrogen-terminated silicone oil is 0.07%, and the hydrogen content of the cross-linked hydrogen silicone oil is 0.17%.

[0007] Furthermore, the preparation method of the modified large-size spherical alumina powder is: Add 200g of large-particle spherical alumina powder with a particle size of 10-30μm and 8g of decyltrimethoxysilane to 100g of anhydrous ethanol, react at a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified large-particle spherical alumina powder.

[0008] Furthermore, the preparation method of the modified small-size spherical alumina powder is: Add 200g of small-particle spherical alumina powder with a particle size of 1-10μm and 5g of silane coupling agent CG12 to 100g of anhydrous ethanol, react at a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified small-particle spherical alumina powder.

[0009] Furthermore, the preparation method of the modified angular alumina powder is: Add 200g of angular alumina powder with a particle size of 1-5μm and 5g of silane coupling agent CG12 to 100g of anhydrous ethanol, react in a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified angular alumina powder.

[0010] Furthermore, the preparation steps of the graphene oxide / boron nitride composite nanosheets include: Step 1, dispersing 2 g of graphene oxide and 2 g of boron nitride nanosheets in 100 g of deionized water respectively, and ultrasonically dispersing at a frequency of 28 kHz for 30 min to obtain a graphene oxide dispersion and a boron nitride nanosheet dispersion; Step 2, dripping the boron nitride nanosheet dispersion into the graphene oxide dispersion at a dripping rate of 2 drops / s, stirring at a stirring speed of 500r / min for 10 minutes, placing in an ultrasonic cleaner at a power of 50W for 10 minutes, and then treating with a power pulse of 50-70W for 5-20 minutes under ice bath conditions, the pulse program is working for 12s and resting for 6s, and finally filtering to remove the filtrate and placing in an oven at 85°C for drying for 12h, and grinding through a 200-mesh sieve to obtain the graphene oxide / boron nitride composite nanosheets.

[0011] Furthermore, the inhibitor is one of vinyl tetracyclic ring and acetylene cyclohexanol, the concentration of the platinum catalyst is 1.00%, and the blue slurry is an oily pigment.

[0012] Furthermore, the preparation method of the main agent system is: S1. Add the above weight portions of low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, terminal hydrogen silicone oil and cross-linked hydrogen silicone oil into a beaker, stir at a stirring speed of 500 r / min for 2 min, then add the above weight portions of inhibitor, continue stirring at the original stirring speed for 2 min, and record it as the silicone oil system; S2. Mix the above-mentioned parts by weight of modified large-particle spherical alumina powder, modified small-particle spherical alumina powder, modified angular alumina powder and graphene oxide / boron nitride composite nanosheets, stir at a stirring speed of 200 r / min for 5 minutes, add the obtained powder into the silicone oil system three times, stir at a stirring speed of 1200 r / min for 2 hours, and then evacuate to remove bubbles, and the result is the main agent system.

[0013] Furthermore, the preparation method of the curing agent system is: Step 1, add the above-mentioned parts by weight of low-viscosity vinyl silicone oil and platinum catalyst into a beaker, stir at a stirring speed of 500r / min for 2 minutes, then add the above-mentioned parts by weight of blue slurry, continue stirring at the original stirring speed for 3 minutes, and record it as the silicone oil component; Step 2. Mix the above-mentioned parts by weight of modified large-particle spherical alumina powder, modified small-particle spherical alumina powder and modified angular alumina powder, stir at a stirring speed of 300 r / min for 5 minutes, add the obtained powder into the silicone oil component three times, stir at a stirring speed of 1200 r / min for 2 hours, and then evacuate to remove bubbles. The result is a curing agent system.

[0014] A method for preparing a high thermal conductivity gel containing a modified filler, the preparation method comprising: The main agent system and the curing agent system are mixed in a weight ratio of (1-3):1, and dispersed by stirring at a stirring speed of 1000 r / min for 5 minutes to obtain a high thermal conductive gel containing modified fillers.

[0015] The present invention provides a high thermal conductivity gel containing modified fillers and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects: 1. The system of the present invention is non-toxic and has no irritating odor, has a small number of components, and a simple preparation method. The main body is organic silica gel, has a moderate curing rate, and is non-selective to the substrate. The silane coupling agent is introduced to modify the thermally conductive filler powder to enhance the compatibility of the particles with the silica gel matrix, and the thermal conductivity of the sample is further improved. Reasonable filler grading helps the filler to form more thermal conductive pathways or thermal conductive networks in the polymer matrix, thereby enhancing the transfer rate of phonons inside the material and enhancing the thermal conductivity of the composite material.

[0016] 2. The present invention can improve the thermal conductive network structure inside the gel by combining modified large-particle spherical alumina powder, modified small-particle spherical alumina powder and modified angular alumina powder. The filler is modified by a modifier to enhance the interfacial bonding between the filler and the silicone oil matrix, thereby improving the thermal conductivity while reducing thermal resistance. Secondly, the present invention can form a multi-level and multi-dimensional filler network by introducing alumina powders and composite nanosheets of different particle sizes and shapes, thereby enhancing the mechanical strength and toughness of the gel. The interaction between the functional groups on the surface of the modified filler and the silicone oil matrix can further enhance the mechanical properties of the gel.

[0017] 3. The composite nanosheets in the present invention combine the high thermal conductivity of graphene oxide and boron nitride, which can further enhance the thermal conductivity of the gel and enable heat to be transferred more quickly; secondly, the platinum catalyst in the present invention can accelerate the cross-linking reaction of the silicone oil system and improve the curing efficiency. Moreover, through the carefully designed components and ratios of the present invention, the main agent system and the curing agent system can be quickly dispersed and cured after mixing to form a stable gel structure. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] The present invention will be further described below in conjunction with the embodiments.

[0020] Embodiment 1: A high thermal conductivity gel containing a modified filler in this embodiment, the high thermal conductivity gel containing a modified filler is composed of a main agent system and a curing agent system; The main agent system is composed of the following components: 7 parts by weight of low-viscosity vinyl silicone oil, 2 parts by weight of high-viscosity vinyl silicone oil, 4 parts by weight of terminal hydrogen silicone oil, 0.1 parts by weight of cross-linked hydrogen silicone oil, 47 parts by weight of modified large-particle spherical alumina powder, 23 parts by weight of modified small-particle spherical alumina powder, 7 parts by weight of modified angular alumina powder, 3 parts by weight of graphene oxide / boron nitride composite nanosheets, and 0.02 parts by weight of inhibitor; The curing agent system consists of the following components: 12 parts by weight of low-viscosity vinyl silicone oil, 47 parts by weight of modified large-particle spherical alumina powder, 23 parts by weight of modified small-particle spherical alumina powder, 7 parts by weight of modified angular alumina powder, 0.1 parts by weight of platinum catalyst and 1 part by weight of blue slurry.

[0021] Among them, the viscosity of low-viscosity vinyl silicone oil is 500cps, and the vinyl content is 0.43%; the viscosity of high-viscosity vinyl silicone oil is 5125cps, and the vinyl content is 0.17%; the hydrogen content of terminal hydrogen silicone oil is 0.07%, and the hydrogen content of cross-linked hydrogen silicone oil is 0.17%.

[0022] The preparation method of modified large-size spherical alumina powder is as follows: Add 200g of large-particle spherical alumina powder with a particle size of 10μm and 8g of decyltrimethoxysilane to 100g of anhydrous ethanol, react in a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain the modified large-particle spherical alumina powder.

[0023] The preparation method of modified small-size spherical alumina powder is as follows: Add 200g of small-particle spherical alumina powder with a particle size of 1μm and 5g of silane coupling agent CG12 to 100g of anhydrous ethanol, react at a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified small-particle spherical alumina powder.

[0024] The preparation method of modified angular alumina powder is: Add 200g of angular alumina powder with a particle size of 1μm and 5g of silane coupling agent CG12 to 100g of anhydrous ethanol, react in a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified angular alumina powder.

[0025] The preparation steps of graphene oxide / boron nitride composite nanosheets include: Step 1, dispersing 2 g of graphene oxide and 2 g of boron nitride nanosheets in 100 g of deionized water respectively, and ultrasonically dispersing at a frequency of 28 kHz for 30 min to obtain a graphene oxide dispersion and a boron nitride nanosheet dispersion; Step 2, dripping the boron nitride nanosheet dispersion into the graphene oxide dispersion at a dripping rate of 2 drops / s, stirring at a stirring speed of 500r / min for 10 minutes, placing in an ultrasonic cleaner for treatment at a power of 50W for 10 minutes, then treating with a power pulse of 50W for 5 minutes under ice bath conditions, the pulse program is working for 12s and resting for 6s, finally filtering to remove the filtrate and placing in an oven at 85°C for drying for 12h, and grinding through a 200-mesh sieve to obtain the graphene oxide / boron nitride composite nanosheets.

[0026] The inhibitor is one of vinyl tetracyclic and acetylene cyclohexanol, the concentration of platinum catalyst is 1.00%, and the blue slurry is oily pigment.

[0027] The preparation method of the main agent system is: S1. Add the above weight portions of low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, terminal hydrogen silicone oil and cross-linked hydrogen silicone oil into a beaker, stir at a stirring speed of 500 r / min for 2 min, then add the above weight portions of inhibitor, continue stirring at the original stirring speed for 2 min, and record it as the silicone oil system; S2. Mix the above-mentioned parts by weight of modified large-particle spherical alumina powder, modified small-particle spherical alumina powder, modified angular alumina powder and graphene oxide / boron nitride composite nanosheets, stir at a stirring speed of 200 r / min for 5 minutes, add the obtained powder into the silicone oil system three times, stir at a stirring speed of 1200 r / min for 2 hours, and then evacuate to remove bubbles, and the result is the main agent system.

[0028] The preparation method of the curing agent system is: Step 1, add the above-mentioned parts by weight of low-viscosity vinyl silicone oil and platinum catalyst into a beaker, stir at a stirring speed of 500r / min for 2 minutes, then add the above-mentioned parts by weight of blue slurry, continue stirring at the original stirring speed for 3 minutes, and record it as the silicone oil component; Step 2. Mix the above-mentioned parts by weight of modified large-particle spherical alumina powder, modified small-particle spherical alumina powder and modified angular alumina powder, stir at a stirring speed of 300 r / min for 5 minutes, add the obtained powder into the silicone oil component three times, stir at a stirring speed of 1200 r / min for 2 hours, and then evacuate to remove bubbles. The result is a curing agent system.

[0029] A method for preparing a high thermal conductivity gel containing a modified filler, the preparation method comprising: The main agent system and the curing agent system are mixed in a weight ratio of 1:1, and are dispersed by stirring at a stirring speed of 1000 r / min for 5 minutes to obtain a high thermal conductive gel containing modified fillers.

[0030] Example 2: A high thermal conductivity gel containing a modified filler in this example, the high thermal conductivity gel containing a modified filler is composed of a main agent system and a curing agent system; The main agent system is composed of the following components: 8 parts by weight of low-viscosity vinyl silicone oil, 3 parts by weight of high-viscosity vinyl silicone oil, 5 parts by weight of terminal hydrogen silicone oil, 0.3 parts by weight of cross-linked hydrogen silicone oil, 49 parts by weight of modified large-particle spherical alumina powder, 25 parts by weight of modified small-particle spherical alumina powder, 9 parts by weight of modified angular alumina powder, 5 parts by weight of graphene oxide / boron nitride composite nanosheets, and 0.04 parts by weight of inhibitor; The curing agent system consists of the following components: 13 parts by weight of low-viscosity vinyl silicone oil, 49 parts by weight of modified large-particle spherical alumina powder, 25 parts by weight of modified small-particle spherical alumina powder, 9 parts by weight of modified angular alumina powder, 0.2 parts by weight of platinum catalyst and 2 parts by weight of blue slurry.

[0031] Among them, the viscosity of low-viscosity vinyl silicone oil is 500cps, and the vinyl content is 0.43%; the viscosity of high-viscosity vinyl silicone oil is 5125cps, and the vinyl content is 0.17%; the hydrogen content of terminal hydrogen silicone oil is 0.07%, and the hydrogen content of cross-linked hydrogen silicone oil is 0.17%.

[0032] The preparation method of modified large-size spherical alumina powder is as follows: Add 200g of large-particle spherical alumina powder with a particle size of 30μm and 8g of decyltrimethoxysilane to 100g of anhydrous ethanol, react at a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified large-particle spherical alumina powder.

[0033] The preparation method of modified small-size spherical alumina powder is as follows: Add 200g of small-particle spherical alumina powder with a particle size of 10μm and 5g of silane coupling agent CG12 to 100g of anhydrous ethanol, react at a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified small-particle spherical alumina powder.

[0034] The preparation method of modified angular alumina powder is: Add 200g of angular alumina powder with a particle size of 5μm and 5g of silane coupling agent CG12 to 100g of anhydrous ethanol, react in a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified angular alumina powder.

[0035] The preparation steps of graphene oxide / boron nitride composite nanosheets include: Step 1, dispersing 2 g of graphene oxide and 2 g of boron nitride nanosheets in 100 g of deionized water respectively, and ultrasonically dispersing at a frequency of 28 kHz for 30 min to obtain a graphene oxide dispersion and a boron nitride nanosheet dispersion; Step 2, dripping the boron nitride nanosheet dispersion into the graphene oxide dispersion at a dripping rate of 2 drops / s, stirring at a stirring speed of 500r / min for 10 minutes, placing in an ultrasonic cleaner at a power of 50W for 10 minutes, and then treating with a power pulse of 70W for 20 minutes under ice bath conditions, the pulse program is working for 12s and resting for 6s, and finally filtering to remove the filtrate and placing in an oven at 85°C for 12h. The obtained graphene oxide / boron nitride composite nanosheets are obtained after grinding through a 200-mesh sieve.

[0036] The inhibitor is one of vinyl tetracyclic and acetylene cyclohexanol, the concentration of platinum catalyst is 1.00%, and the blue slurry is oily pigment.

[0037] The preparation method of the main agent system is: S1. Add the above weight portions of low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, terminal hydrogen silicone oil and cross-linked hydrogen silicone oil into a beaker, stir at a stirring speed of 500 r / min for 2 min, then add the above weight portions of inhibitor, continue stirring at the original stirring speed for 2 min, and record it as the silicone oil system; S2. Mix the above-mentioned parts by weight of modified large-particle spherical alumina powder, modified small-particle spherical alumina powder, modified angular alumina powder and graphene oxide / boron nitride composite nanosheets, stir at a stirring speed of 200 r / min for 5 minutes, add the obtained powder into the silicone oil system three times, stir at a stirring speed of 1200 r / min for 2 hours, and then evacuate to remove bubbles, and the result is the main agent system.

[0038] The preparation method of the curing agent system is: Step 1, add the above-mentioned parts by weight of low-viscosity vinyl silicone oil and platinum catalyst into a beaker, stir at a stirring speed of 500r / min for 2 minutes, then add the above-mentioned parts by weight of blue slurry, continue stirring at the original stirring speed for 3 minutes, and record it as the silicone oil component; Step 2. Mix the above-mentioned parts by weight of modified large-particle spherical alumina powder, modified small-particle spherical alumina powder and modified angular alumina powder, stir at a stirring speed of 300 r / min for 5 minutes, add the obtained powder into the silicone oil component three times, stir at a stirring speed of 1200 r / min for 2 hours, and then evacuate to remove bubbles. The result is a curing agent system.

[0039] A method for preparing a high thermal conductivity gel containing a modified filler, the preparation method comprising: The main agent system and the curing agent system are mixed in a weight ratio of 3:1, and dispersed by stirring at a stirring speed of 1000 r / min for 5 minutes to obtain a high thermal conductive gel containing modified fillers.

[0040] Embodiment 3: A high thermal conductivity gel containing a modified filler in this embodiment, the high thermal conductivity gel containing a modified filler is composed of a main agent system and a curing agent system; The main agent system is composed of the following components: 7.5 parts by weight of low-viscosity vinyl silicone oil, 2.5 parts by weight of high-viscosity vinyl silicone oil, 4.5 parts by weight of terminal hydrogen silicone oil, 0.2 parts by weight of cross-linked hydrogen silicone oil, 48 parts by weight of modified large-particle spherical alumina powder, 24 parts by weight of modified small-particle spherical alumina powder, 8 parts by weight of modified angular alumina powder, 4 parts by weight of graphene oxide / boron nitride composite nanosheets, and 0.03 parts by weight of inhibitor; The curing agent system consists of the following components: 12.5 parts by weight of low-viscosity vinyl silicone oil, 48 parts by weight of modified large-particle spherical alumina powder, 24 parts by weight of modified small-particle spherical alumina powder, 8 parts by weight of modified angular alumina powder, 0.15 parts by weight of platinum catalyst and 1.5 parts by weight of blue slurry.

[0041] Among them, the viscosity of low-viscosity vinyl silicone oil is 500cps, and the vinyl content is 0.43%; the viscosity of high-viscosity vinyl silicone oil is 5125cps, and the vinyl content is 0.17%; the hydrogen content of terminal hydrogen silicone oil is 0.07%, and the hydrogen content of cross-linked hydrogen silicone oil is 0.17%.

[0042] The preparation method of modified large-size spherical alumina powder is as follows: Add 200g of large-particle spherical alumina powder with a particle size of 20μm and 8g of decyltrimethoxysilane to 100g of anhydrous ethanol, react at a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified large-particle spherical alumina powder.

[0043] The preparation method of modified small-size spherical alumina powder is as follows: Add 200g of small-particle spherical alumina powder with a particle size of 5μm and 5g of silane coupling agent CG12 to 100g of anhydrous ethanol, react at a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified small-particle spherical alumina powder.

[0044] The preparation method of modified angular alumina powder is: Add 200g of angular alumina powder with a particle size of 3μm and 5g of silane coupling agent CG12 to 100g of anhydrous ethanol, react in a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified angular alumina powder.

[0045] The preparation steps of graphene oxide / boron nitride composite nanosheets include: Step 1, dispersing 2 g of graphene oxide and 2 g of boron nitride nanosheets in 100 g of deionized water respectively, and ultrasonically dispersing at a frequency of 28 kHz for 30 min to obtain a graphene oxide dispersion and a boron nitride nanosheet dispersion; Step 2, dripping the boron nitride nanosheet dispersion into the graphene oxide dispersion at a dripping rate of 2 drops / s, stirring at a stirring speed of 500r / min for 10 minutes, placing in an ultrasonic cleaner at a power of 50W for 10 minutes, and then treating with a power pulse of 60W for 13 minutes under ice bath conditions, the pulse program is working for 12s and resting for 6s, and finally filtering to remove the filtrate and placing in an oven at 85°C for 12h. The obtained graphene oxide / boron nitride composite nanosheets are obtained after grinding through a 200-mesh sieve.

[0046] The inhibitor is one of vinyl tetracyclic and acetylene cyclohexanol, the concentration of platinum catalyst is 1.00%, and the blue slurry is oily pigment.

[0047] The preparation method of the main agent system is: S1. Add the above weight portions of low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, terminal hydrogen silicone oil and cross-linked hydrogen silicone oil into a beaker, stir at a stirring speed of 500 r / min for 2 min, then add the above weight portions of inhibitor, continue stirring at the original stirring speed for 2 min, and record it as the silicone oil system; S2. Mix the above-mentioned parts by weight of modified large-particle spherical alumina powder, modified small-particle spherical alumina powder, modified angular alumina powder and graphene oxide / boron nitride composite nanosheets, stir at a stirring speed of 200 r / min for 5 minutes, add the obtained powder into the silicone oil system three times, stir at a stirring speed of 1200 r / min for 2 hours, and then evacuate to remove bubbles, and the result is the main agent system.

[0048] The preparation method of the curing agent system is: Step 1, add the above-mentioned parts by weight of low-viscosity vinyl silicone oil and platinum catalyst into a beaker, stir at a stirring speed of 500r / min for 2 minutes, then add the above-mentioned parts by weight of blue slurry, continue stirring at the original stirring speed for 3 minutes, and record it as the silicone oil component; Step 2. Mix the above-mentioned parts by weight of modified large-particle spherical alumina powder, modified small-particle spherical alumina powder and modified angular alumina powder, stir at a stirring speed of 300 r / min for 5 minutes, add the obtained powder into the silicone oil component three times, stir at a stirring speed of 1200 r / min for 2 hours, and then evacuate to remove bubbles. The result is a curing agent system.

[0049] A method for preparing a high thermal conductivity gel containing a modified filler, the preparation method comprising: The main agent system and the curing agent system are mixed in a weight ratio of 2:1, and are dispersed by stirring at a stirring speed of 1000 r / min for 5 minutes to obtain a high thermal conductive gel containing modified fillers.

[0050] Comparative Example 1: A high thermal conductivity gel containing modified filler and a preparation method thereof provided in this comparative example are roughly the same as those in Example 1, with the main difference being that in this comparative example 1, the composition of the main agent system in Example 1 is changed to: 8 parts by weight of low-viscosity vinyl silicone oil, 3 parts by weight of high-viscosity vinyl silicone oil, 5 parts by weight of terminal hydrogen silicone oil, 0.3 parts by weight of cross-linked hydrogen silicone oil, 80 parts by weight of modified large-particle spherical alumina powder and 0.04 parts by weight of inhibitor vinyl tetracyclic body; in this comparative example 1, the composition of the curing agent system in Example 1 is changed to: 13 parts by weight of low-viscosity vinyl silicone oil, 80 parts by weight of modified large-particle spherical alumina powder, 0.2 parts by weight of platinum catalyst and 2 parts by weight of blue slurry.

[0051] Comparative Example 2: A high thermal conductivity gel containing modified fillers and a preparation method thereof provided in this comparative example are roughly the same as those in Example 1, with the main difference being that in this comparative example 2, the composition of the main agent system in Example 1 is changed to: 8 parts by weight of low-viscosity vinyl silicone oil, 3 parts by weight of high-viscosity vinyl silicone oil, 5 parts by weight of terminal hydrogen silicone oil, 0.3 parts by weight of cross-linked hydrogen silicone oil, 80 parts by weight of modified small-particle spherical alumina powder and 0.04 parts by weight of inhibitor acetylene cyclohexanol; in this comparative example 2, the composition of the curing agent system in Example 1 is changed to: 13 parts by weight of low-viscosity vinyl silicone oil, 80 parts by weight of modified small-particle spherical alumina powder, 0.2 parts by weight of platinum catalyst and 2 parts by weight of blue slurry.

[0052] Comparative Example 3: A high thermal conductivity gel containing modified filler and a preparation method thereof provided in this comparative example are roughly the same as those in Example 1, with the main difference being that in this comparative example 3, the composition of the main agent system in Example 1 is changed to: 8 parts by weight of low viscosity vinyl silicone oil, 3 parts by weight of high viscosity vinyl silicone oil, 5 parts by weight of terminal hydrogen silicone oil, 0.3 parts by weight of cross-linked hydrogen silicone oil, 80 parts by weight of modified angular alumina powder and 0.04 parts by weight of inhibitor acetylene cyclohexanol; in this comparative example 3, the composition of the curing agent system in Example 1 is changed to: 13 parts by weight of low viscosity vinyl silicone oil, 80 parts by weight of modified angular alumina powder, 0.2 parts by weight of platinum catalyst and 2 parts by weight of blue slurry.

[0053] Performance test: The high thermal conductive gels containing modified fillers prepared in Examples 1-3 and Comparative Examples 1-3 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, respectively, and then the performance of Examples 1-3 and Comparative Examples 1-3 is tested. The specific testing methods and test items are as follows: 1. The curing time of Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard of GB / T 11026-2016, and the obtained data were recorded in the following table; 2. The thermal conductivity of Examples 1-3 and Comparative Examples 1-3 was tested according to the standard of GB / T 10294-2008, and the obtained data were recorded in the following table; 3. The volume resistivity of Examples 1-3 and Comparative Examples 1-3 was tested according to the standard of GB / T 1410-2006, and the obtained data were recorded in the following table; 4. The dielectric strength of Examples 1-3 and Comparative Examples 1-3 was tested according to the standard of GB / T 1408.1-2016, and the obtained data are recorded in the following table;

[0054] It can be seen from the data in the above table that the curing time in Examples 1-3 is significantly higher than that in Comparative Example 1, indicating that acetylene cyclohexanol has a better inhibitory effect, a long curing time, and is more beneficial to cost saving; Examples 1-3 have higher thermal conductivity than Comparative Example 1-3, indicating that the ratio of powders in Examples 1-3 can play a better role in improving thermal conductivity; when all fillers use modified large-particle spherical alumina powder, the thermal conductivity is reduced, and the extrusion rate of the high thermal conductivity gel is very low, affecting subsequent construction; when all fillers use modified small-particle spherical alumina powder or modified angular alumina powder, the thermal conductivity is significantly reduced, but the extrusion rate is increased. When the three fillers are used in combination, the thermal conductivity reaches the highest and the extrusion rate is moderate.

[0055] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0056] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high thermal conductivity gel containing modified fillers, characterized in that: The high thermal conductivity gel containing modified fillers is composed of a main agent system and a curing agent system; The main agent system is composed of the following components: 7-8 parts by weight of low-viscosity vinyl silicone oil, 2-3 parts by weight of high-viscosity vinyl silicone oil, 4-5 parts by weight of terminal hydrogen silicone oil, 0.1-0.3 parts by weight of cross-linked hydrogen silicone oil, 47-49 parts by weight of modified large-particle spherical alumina powder, 23-25 ​​parts by weight of modified small-particle spherical alumina powder, 7-9 parts by weight of modified angular alumina powder, 3-5 parts by weight of graphene oxide / boron nitride composite nanosheets, and 0.02-0.04 parts by weight of inhibitor; The curing agent system is composed of the following components: 12-13 parts by weight of low-viscosity vinyl silicone oil, 47-49 parts by weight of modified large-particle spherical alumina powder, 23-25 ​​parts by weight of modified small-particle spherical alumina powder, 7-9 parts by weight of modified angular alumina powder, 0.1-0.2 parts by weight of platinum catalyst and 1-2 parts by weight of blue slurry.

2. The high thermal conductivity gel containing modified fillers according to claim 1, characterized in that: The viscosity of the low-viscosity vinyl silicone oil is 500 cps, and the vinyl content is 0.43%. The viscosity of the high-viscosity vinyl silicone oil is 5125 cps, and the vinyl content is 0.17%. The hydrogen content of the hydrogen-terminated silicone oil is 0.07%, and the hydrogen content of the cross-linked hydrogen silicone oil is 0.17%.

3. The high thermal conductivity gel containing modified fillers according to claim 1, characterized in that: The preparation method of the modified large-diameter spherical alumina powder is as follows: Add 200g of large-particle spherical alumina powder with a particle size of 10-30μm and 8g of decyltrimethoxysilane to 100g of anhydrous ethanol, react at a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified large-particle spherical alumina powder.

4. The high thermal conductivity gel containing modified fillers according to claim 1, characterized in that: The preparation method of the modified small-size spherical alumina powder is as follows: Add 200g of small-particle spherical alumina powder with a particle size of 1-10μm and 5g of silane coupling agent CG12 to 100g of anhydrous ethanol, react at a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified small-particle spherical alumina powder.

5. The high thermal conductivity gel containing modified fillers according to claim 1, characterized in that: The preparation method of the modified angular alumina powder is: Add 200g of angular alumina powder with a particle size of 1-5μm and 5g of silane coupling agent CG12 to 100g of anhydrous ethanol, react in a water bath temperature of 80°C for 48h, filter and remove the filtrate, place it in a forced air drying oven at 130°C and dry it for 8h, then grind it through a 200-mesh sieve to obtain modified angular alumina powder.

6. The high thermal conductivity gel containing modified fillers according to claim 1, characterized in that: The preparation steps of the graphene oxide / boron nitride composite nanosheets include: Step 1, dispersing 2 g of graphene oxide and 2 g of boron nitride nanosheets in 100 g of deionized water respectively, and ultrasonically dispersing at a frequency of 28 kHz for 30 min to obtain a graphene oxide dispersion and a boron nitride nanosheet dispersion; Step 2, dripping the boron nitride nanosheet dispersion into the graphene oxide dispersion at a dripping rate of 2 drops / s, stirring at a stirring speed of 500r / min for 10 minutes, placing in an ultrasonic cleaner at a power of 50W for 10 minutes, and then treating with a power pulse of 50-70W for 5-20 minutes under ice bath conditions, the pulse program is working for 12s and resting for 6s, and finally filtering to remove the filtrate and placing in an oven at 85°C for drying for 12h, and grinding through a 200-mesh sieve to obtain the graphene oxide / boron nitride composite nanosheets.

7. The high thermal conductivity gel containing modified fillers according to claim 1, characterized in that: The inhibitor is one of vinyl tetracyclic and acetylene cyclohexanol, the concentration of the platinum catalyst is 1.00%, and the blue slurry is an oily pigment.

8. The high thermal conductivity gel containing modified fillers according to claim 1, characterized in that: The preparation method of the main agent system is: S1. Add the above weight portions of low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, terminal hydrogen silicone oil and cross-linked hydrogen silicone oil into a beaker, stir at a stirring speed of 500 r / min for 2 min, then add the above weight portions of inhibitor, continue stirring at the original stirring speed for 2 min, and record it as the silicone oil system; S2. Mix the above-mentioned parts by weight of modified large-particle spherical alumina powder, modified small-particle spherical alumina powder, modified angular alumina powder and graphene oxide / boron nitride composite nanosheets, stir at a stirring speed of 200 r / min for 5 minutes, add the obtained powder into the silicone oil system three times, stir at a stirring speed of 1200 r / min for 2 hours, and then evacuate to remove bubbles, and the result is the main agent system.

9. The high thermal conductivity gel containing modified fillers according to claim 1, characterized in that: The preparation method of the curing agent system is: Step 1, add the above-mentioned parts by weight of low-viscosity vinyl silicone oil and platinum catalyst into a beaker, stir at a stirring speed of 500r / min for 2 minutes, then add the above-mentioned parts by weight of blue slurry, continue stirring at the original stirring speed for 3 minutes, and record it as the silicone oil component; Step 2. Mix the above-mentioned parts by weight of modified large-particle spherical alumina powder, modified small-particle spherical alumina powder and modified angular alumina powder, stir at a stirring speed of 300 r / min for 5 minutes, add the obtained powder into the silicone oil component three times, stir at a stirring speed of 1200 r / min for 2 hours, and then evacuate to remove bubbles. The result is a curing agent system.

10. A method for preparing a high thermal conductive gel containing a modified filler according to any one of claims 1 to 9, characterized in that: The preparation method is: The main agent system and the curing agent system are mixed in a weight ratio of (1-3):1, and dispersed by stirring at a stirring speed of 1000 r / min for 5 minutes to obtain a high thermal conductive gel containing modified fillers.

Citation Information

Patent Citations

  • Graphene-containing heat conduction gel as well as preparation method and application

    CN108148558A

  • Addition type heat-conducting pouring sealant and preparation method thereof

    CN115340844A

  • Single-component heat-conducting gel and preparation method thereof

    CN116355424A

  • Inorganic non-metallic nanoparticle-assembled hydrogel material and application thereof in additive manufacturing technology

    WO2022252526A1

Cited By

  • Thermoplastic heat dissipation material based on modified aluminum oxide as well as preparation method and application of thermoplastic heat dissipation material

    CN121226905A

  • Thermoplastic heat dissipation material based on modified alumina and preparation method and application thereof

    CN121226905B